Friction/Reward : be your customer's first choice - Hammond, Richard (Retail management consultant) (Pearson, 2019)
Richard Hammond is a retailing expert, and Smart Circle is his problem-solving consultancy. Together with select subject-matter experts he tackles a wide range of retail challenges: from 'big idea' and format development to customer engagement and retail futurology. He is also the author of Smart Retail 4e.